FAMILY STRATIOMYIDAE - Fachin, Diego Aguilar; de Assis-Pujol, Cristiane Vieira (Zootaxa, 2016)
The family Stratiomyidae has more than 2,800 described species, of which 1001 species belongs to the Neotropics. This catalog for Colombia presents 87 species distributed in 32 genera, and ten subfamilies. Merosargus gracilis and the genus Microchrysa, with a single species M. bicolor are recorded for the first time to Colombia. The fauna is very expressive but still poorly known, representing nearly one tenth of the Neotropical diversity of the family in numbers of species, and one fifth of generic diversity.